The effect of group vocal and singing exercises for vocal and speech deficits in individuals with Parkinson's disease: a pilot study - Azekawa, Megumi, author; LaGasse, Ashley Blythe, advisor; Davis, William B. (William Barron), committee member; Fails, Anna Dee, committee member (Colorado State University. Libraries, 2011)
Although the majority of individuals with Parkinson's disease (PD) develop characteristics of hypokinetic dysarthria during the course of the disease, there is no known treatment that provides consistent efficacy. The purpose of this study was to investigate the effect of the Music Therapy Treatment Protocol for Hypokinetic Dysarthria (MTPHD), which utilized two neurologic music therapy (NMT) techniques for treating voice and speech characteristics developed due to hypokinetic dysarthria. Five participants with PD exhibiting characteristics of hypokinetic dysarthria participated in six weekly group music therapy sessions. Three speech assessments were administered as pretest and posttest to assess participants' improvement in variables that measured vocal function, voice quality, articulatory control, and connected speech intelligibility through acoustic and perceptual analyses. A paired samples t-test exhibited significant differences at posttest in the number of inter-word pauses, total inter-word pause time, and speaking fundamental frequency. No other significant differences were observed. Suggestions for future research are discussed.
Keywords: dysarthria; singing; rehabilitation; music therapy; Parkinson's disease